Leucine supplementation and intensive training - Mero, A. (Sports Medicine, 1999)
Consumption of BCAA (30 to 35% leucine) before or during endurance exercise may prevent or decrease the net rate of protein degradation, may improve both mental and physical performance and may have a sparing effect on muscle glycogen degradation and depletion of muscle glycogen stores. However, leucine supplementation (200 mg/kg bodyweight) 50 minutes before anaerobic running exercise had no effect on performance. During 5 weeks of strength and speed training, leucine supplementation of 50 mg/kg bodyweight/day, supplementary to a daily protein intake of 1.26 g/kg bodyweight/day, appeared to prevent the decrease in the serum leucine levels in power-trained athletes. According to 1 study, dietary supplementation of the leucine metabolite beta-hydroxy-beta-methylbutyrate (HMB) 3 g/day to humans undertaking intensive resistance training exercise resulted in an increased deposition of fat-free mass and an accompanying increase in strength. Muscle proteolysis was also decreased with HMB, accompanied by lower plasma levels of enzymes indicating muscle damage and an average 50% decrease in plasma essential amino acid levels. Furthermore, BCAA supplementation (76% leucine) in combination with moderate energy restriction has been shown to induce significant and preferential losses of visceral adipose tissue and to allow maintenance of a high level of performance.